Eksistensi Permainan Tradisional sebagai Aktivitas Fisik Anak Usia Dini Pada Generasi Alfa - Cahniyo Wijaya Kuswanto; Dona Dinda Pratiwi; Galuh Yuliar Denata (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2022)
Currently, in the alpha era of early childhood born in the 2010 with the advancement of the era and technological developments, traditional games that involve physical activity are barely carried out at home or at school and traditional games have begun to be eroded and neglected since the alpha generation got to know gadgets and the internet, because it is more fun to play. The purpose of this study was to determine the existence of traditional games as a physical activity for early childhood in the alpha era. This study uses mixed methods (Mixed Methods) as the research method with research designs including: (1) Exploratory Design Source (2) Explanatory Design Source (3) Triangulation Design Source, as well as data analysis using a Likert scale and assisted by SPSS version 23. The results show that the existence of traditional games has the support of the community and schools to make traditional games exist whenever and wherever, there are some areas of traditional games that need support from all parties, both family and school so that these traditional games continue to exist in the alpha era. Findings in the field indicate that there needs to be leeway from all parties (teachers, parents, community) to give time, land, and attention to early childhood children to play traditional games in the surrounding environment, both at school and at home.Keyword: the existence of traditional games; physical activity; alpha era